Regenerasi Kinerja Fluks Membran PVDF Ultrafiltrasi Menggunakan Kombinasi Asam Sitrat & H2O2 Dalam Pengolahan Air Sungai Jagir - Pamungkas, Kresna Setyawan Adhi; Jawwad, Muhammad Abdus Salam (Jurnal Serambi Engineering, 2026)
Polyvinylidene fluoride (PVDF)-based ultrafiltration membranes are widely used because they can remove suspended and dissolved contaminants from water. However, fouling remains a major challenge, causing flux reduction and shortening the lifespan of the membrane. This study evaluated the performance of PVDF membranes when filtering Jagir River water, and assessed the effectiveness of stepwise washing with citric acid (C₆H₈O₇) and hydrogen peroxide (H₂O₂). Experiments were conducted at operating pressures of 1, 1.5 and 2 bar. Membrane flux was measured under four operating conditions: initial flux using distilled water (Jw1); river water flux before washing; flux using distilled water after washing (Jw2); and river water flux after washing. The results showed that Jw1 increased with increasing pressure, reaching a maximum value at 2 bar. However, river water filtration caused a significant decrease in flux due to fouling. Stepwise chemical washing partially recovered the flux, as indicated by the increases in Jw₂ and river water flux after washing. However, full recovery was limited by irreversible fouling. The highest Flux Recovery Ratio (FRR) value was obtained at 2 bar with a 6 wt% washing solution, indicating that the combination of high pressure and chemical treatment provides optimal performance recovery. Overall, the PVDF membrane can be effectively regenerated using citric acid and hydrogen peroxide; however, organic and inorganic mixed fouling limits total flux recovery.